Photocatalytic and antimicrobial multifunctional nanocomposite membranes for emerging pollutants water treatment applications. (July 2020) - Salazar, H.; Martins, P.M.; Santos, Bruno; Fernandes, M.M.; Reizabal, Ander; Sebastián, Víctor; Botelho, G.; Tavares, Carlos J.; Vilas-Vilela, José L.; Lanceros-Mendez, S.
Abstract: Emerging pollutants represent a new global problem for water quality. As these compounds get into the environment, they cause severe threats to aquatic environments and human health and are typically resistant to conventional wastewater treatments. In this work, TiO2 nanoparticles surface was functionalized with silver (Ag) nanoparticles, and solvent cast and electrospun membranes of poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) were prepared with different concentrations of TiO2 and Ag–TiO2 to produce a multifunctional material. The photocatalytic activity of the nanocomposites was evaluated through the degradation of norfloxacin under ultraviolet (UV) and visible radiation. It is shown that nanocomposites with Ag–TiO2 show the highest degradation efficiencies: 64.2% under UV and 80.7% under visible radiation, for 90 and 300 min, respectively. Furthermore, the recyclability of the membranes has also been demonstrated. Finally, it is shown the antimicrobial activity of the nanocomposite membranes, demonstrating the suitability of the Ag–TiO2 /PVDF-HFP nanocomposites as multifunctional photocatalytic and antimicrobial membranes for water remediation applications. Graphical abstract: Image 1 Highlights: Synthesis of Ag–TiO2 nanocomposites with ability to absorb visible radiation. Production of Ag–TiO2 /PVDF-HFP membranes with different morphologies. Photocatalytic efficiency tested with norfloxacin under visible and UV radiation. Antimicrobial tests were performed against two bacteria species (gram + and gram -).